Use of Onlay Hydroxyapatite Cement for Secondary Cranioplasty. Issue 1 (January 2021) - Brussius Coelho, Marcio; Rtshiladze, Michael; Aggarwala, Shivani; Hunt, Jeremy; Peltz, Tim; Gardner, Danielle; Gianoutsos, Mark
Abstract : Background: Children who undergo bi-fronto-orbital advancement (BFOA) frequently develop a contour deformity on the temporal and supra-orbital region, with an incidence reported as high as 55% and 75%, respectively. Up to 20% of patients may require correction. Hydroxyapatite cement (HAC) is a good alternative to autogenous tissue. The available literature on its use focusses on the reconstruction of bone defects, but little has been published on its efficacy and safety as an onlay graft over intact cranium. Objectives: To describe our institution's experience with HAC in the pediatric population. Methods: Retrospective chart review from 1998 to 2018 on all patients from the Craniofacial Unit at the Sydney Children's Hospital who had either coronal or metopic craniosynostosis and underwent BFOA and later in life required cranioplasty with HAC for contour repair. Findings: We have performed 166 BFOA and nineteen secondary cranioplasties for contour repair using onlay HAC. The mean age at the time of operation was 14 years. Bi-coronal craniosynostosis was most frequently associated with secondary cranioplasty and 37% had an associated syndrome. The mean volume of HAC used was 37 mL. There was only 1 patient who had a complication (5.3%) and required partial removal of allograft. The mean length of admission was 2 days. Mean follow up time of 22.4 months. Conclusions: HAC represents a safe option when used correctly, with low rates of complication and satisfactory cosmetic outcomes. Abstract : Supplemental Digital Content is available in the text